Pengaruh Literasi Zakat dan Kepercayaan Muzakki terhadap Keputusan Membayar Zakat di Baznas Kabupaten Tanjung Jabung Barat: Studi pada Masyarakat Kecamatan Tungkal Ilir - Aulia Taufig Kurrahman; Arsa Arsa; Beid Fitrianova Andriani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
A decision is something that motivates someone to do something they want to do and it is influenced by their habits and personality. Decisions are influenced by two factors, including knowledge (literacy) and trust (belief). This research aims to determine the influence of zakat literacy and muzakki beliefs on the muzakki's decision to pay zakat in Baznas, West Tanjung Jabung Regency (study in the community of Tungkal Ilir District). The method in this research is quantitative research. The samples were taken using nonprobability techniques. The analysis used is multiple linear regression with the SPSS 27 program. The research results show that zakat literacy (X1) partially has a positive and significant effect on decisions (Y), muzakki trust (X2) partially has a positive and significant effect on decisions (Y). Meanwhile, simultaneously zakat literacy and muzakki beliefs have a positive and significant influence on muzakki's decision to pay zakat in Baznas, West Tanjung Jabung Regency (study of the Tungkal Ilir District community).